2017
DOI: 10.1037/apl0000176
|View full text |Cite
|
Sign up to set email alerts
|

The structure of group task performance—A second look at “collective intelligence”: Comment on Woolley et al. (2010).

Abstract: Collective intelligence has been described as a general factor that "explains a group's performance on a wide variety of tasks" (Woolley, Chabris, Pentland, Hashmi, & Malone, 2010, p. 686), much like the general intelligence factor explains individuals' performance on cognitive ability tasks. This construct has received widespread attention in both the media and academic community. In this article we reexamine the data from 6 previously published samples that have been used to examine the existence of the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Skill diversity (i.e., variance in group members' ability) has been shown to both enhance [98] and handicap collective performance [18,67,60]. Similar inconsistencies arise for cognitive style diversity [118,150,3], social perceptiveness [217,69,72,120], and even the relative performance of teams versus individuals [48,190,219].…”
Section: Premise: a Unifying Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Skill diversity (i.e., variance in group members' ability) has been shown to both enhance [98] and handicap collective performance [18,67,60]. Similar inconsistencies arise for cognitive style diversity [118,150,3], social perceptiveness [217,69,72,120], and even the relative performance of teams versus individuals [48,190,219].…”
Section: Premise: a Unifying Theorymentioning
confidence: 99%
“…As organizations have moved inexorably to more team-based structures, the problem of improving team performance through judicious selection of team members has preoccupied management scientists and managers alike [115,2,101,197,145]. Previous research has found a variety of intriguing results regarding the impact of skill diversity [98], cognitive style diversity [68], and social perceptiveness [110,217] is little consensus on whether teams always outperform independent individuals (i.e., the relative performance of teams versus individuals) [48,219,190].…”
Section: Environments Of Widely Varying Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…A seminal study by Woolley et al (2010) suggested that small groups may be treated as collective subjects with their own level of collective intelligence, and that this level does not correlate with either the average or the best individual intelligence of the group members, but may be predicted by gender, average social sensitivity, and in-group discussion style. As the replicability of this phenomenon is still debated (Bates and Gupta, 2017;Credé and Howardson, 2017) the question arises of what conditions are necessary for the collective intelligence to emerge, and whether it can be revealed in computer-directed communication or via face-to-face interaction only (Engel, 2015; Barlow and Dennis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lot of empirical evidence about the CI general factor, some scholars have tried to resize its effects on groups' problem-solving performance [7,8]. In particular, a recent re-analysis of the four main empirical studies in the field of CI [4,[9][10][11] does not support the hypothesis of a general factor able to explain the performance variation across a wide variety of group-based tasks [8]. Studies carried out in the online environment show that it manifests differently depending on context [9].…”
Section: Introductionmentioning
confidence: 99%